Kinetta - Lanthimos, Yorgos; Bakatakis, Thimios; Randou, Evangelia; Servetalis, Aris; Xikominos, Kostas (Second Run, 2015)
Kinetta ... a desolate Greek resort town, inhabited during the off-season by migrant workers. In this colourless setting, the film studies the cryptic activities of an inscrutable trio: a plain-clothes cop with a passion for cars, tape recorders and Russian women; a loner clerk who is a part-time photographer; and a hotel maid with aspirations to be an actress. They barely speak, passing the time by staging outlandish re-enactments of local murders. Their efforts are obsessive, the details exhaustive, their purpose ... questionable. Available for the first time anywhere in the world on home video, this darkly comic and compellingly hypnotic film is the extraordinary debut feature of Yorgos Lanthimos ("Dogtooth", "Alps" and "The Lobster"), one of Greek cinema's most acclaimed new directors. [Cover]